279Val→Phe Polymorphism of lipoprotein-associated phospholipase A2 resulted in changes of folding kinetics and recognition to substrate. (December 2015) - Masbuchin, Ainun Nizar; Rohman, Mohammad Saifur; Putri, Jayarani Fatimah; Cahyaningtyas, Miryanti; Widodo,
Graphical abstract: Highlights: The PLA2G7 279F allele was associated with a reduced MI risk of 78% [OR 0.22 (0.035–1.37)] The folding simulation suggested a decreased percentage of α-helix, hydrogen bond formation, hydrogen bond stability in 279 Val→Phe The phosphatydilcholine did not interact with active site of 279 Val→Phe as paradoxically observed in 279 valine Molecular dynamics simulations also indicated that 279 Val→Phe Polymorphism resulted in unstable binding to the substrate and decrease the enzymatic activity Abstract: Introduction: PLA2G7 encodes Lp-PLA2 having role in the formation of atherosclerotic plaques by catalyzing its substrate, phosphatydilcholine (PC), to be pro-inflammatory substances. The increased risk for coronary artery disease (CAD) in Asian population has been related with this enzyme. 279 Val→Phe variant was reported to have a protective role against CAD due to, in part, secretion defect or loss of enzymatic function. Therefore, We study folding kinetics and enzyme-substrate interaction in 279 Val→Phe by using clinical and computational biology approach. Methods: Polymorphisms were detected by genotyping among 103 acute myocardial infarction patients and 37 controls. Folding Lp-PLA2 was simulated using GROMACS software by assessing helicity, hydrogen bond formation and stability. The interactions of Lp-PLA2 and its substrate were simulated using Pyrx software followed by molecular dynamics simulation using YASARA software. Result: Polymorphism of 279 Val→Phe was represented by the change of nucleotide from G to T of 994th PLA2G7 gene. The folding simulation suggested a decreased percentage of α-helix, hydrogen bond formation, hydrogen bond stability and hydrophobicity in 279 Val→Phe . The PC did not interact with active site of 279 Val→Phe as paradoxically observed in 279 valine. 279 Val→Phe polymorphism is likely to cause unstable binding to the substrate and decrease the enzymatic activity as observed in molecular dynamics simulations. The results of our computational biology study supported a protected effect of 279 Val→Phe Polymorphism showed by the odd ratio for MI of 0.22 (CI 95% 0.035–1.37) in this study. Conclusion: 279 Val→Phe Polymorphism of Lp-PLA2 may lead to decrease the enzymatic activity via changes of folding kinetics and recognition to its substrate.